Biomarkers of genotoxicity, immunotoxicity and oxidative stress on Caiman latirostris (Broad-snouted caiman) hatchlings exposed to pesticide formulations and mixtures widely used in agriculture - López González, Evelyn Cecilia (2021)
Pesticide formulations are currently considered as one of the main factors responsible for environmental contamination worldwide. Consequently, several wild species can be affected by the over use of pesticides related to agriculture activity. The aim of this study was to evaluate genotoxicity, immunotoxicity and oxidative stress on Caiman latirostris hatchlings exposed in vivo to sub-lethal concentrations of three insecticide formulations: Endosulfan (END)-, Cypermethrin (CYP)-, and Chlorpyrifos (CPF)- based formulations, two Glyphosate (GLY)- based herbicide formulations and two different ternary complex mixtures of them. C. latirostris hatchlings, 20 days old were exposed in plastics containers with pesticide solutions (by voluntary immersion) during two months, with a progressive decrease in pesticide concentrations through time, in order to simulate their degradation in water under natural conditions. After exposure, blood samples were taken to all animals for the analysis of genotoxicity (Comet assay, Micronucleus and other nuclear abnormalities) immunotoxicity (Total and differential white blood cell counts) and oxidative stress (Lipoperoxidation and the antioxidant enzymes Catalase and Superoxide dismutase). Results indicated that the five formulations tested, as well as the complex mixtures of them, induced genotoxicity, alteration in white blood cell counts and oxidative stress at environmentally relevant concentrations. Mixtures showed different interactions depending of the biomarker analyzed. This study constitutes an integral evaluation of the effect of five pesticide formulations and two possible complex ternary mixtures widely used in soybean crops in Argentina, on different endpoints on a native reptile species, C. latirostris.